2000
DOI: 10.1128/iai.68.11.6250-6256.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Structure of Outer Membrane Protein E of Moraxella catarrhalis and Construction and Characterization of Mutants

Abstract: Outer membrane protein E (OMP E) is a 50-kDa protein of Moraxella catarrhalis which possesses several characteristics indicating that the protein will be an effective vaccine antigen. To study the antigenic structure of OMP E, eight monoclonal antibodies were developed and characterized. Three of the antibodies recognized epitopes which are present on the bacterial surface. Fusion peptides corresponding to overlapping regions of OMP E were constructed, and immunoblot assays were performed to localize the areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The identity of the gene product(s) responsible for this phenotype has been the subject of much research interest over the past decade, and it was first suggested by Verduin et al (54) that a proteinaceous substance on the surface of M. catarrhalis was responsible for complement resistance. Initial studies attempting to identify either the proposed resistance factor or the mechanism of resistance utilized serum-resistant and serum-sensitive clinical isolates (8,54,55), and only in the past few years have isogenic parent-mutant pairs been tested (3,14,22,36,60). These studies indicated that there were several mutations affecting The results of the present study showed that UspA2 is directly involved in the expression of serum resistance by some strains of M. catarrhalis.…”
Section: Discussionmentioning
confidence: 81%
“…The identity of the gene product(s) responsible for this phenotype has been the subject of much research interest over the past decade, and it was first suggested by Verduin et al (54) that a proteinaceous substance on the surface of M. catarrhalis was responsible for complement resistance. Initial studies attempting to identify either the proposed resistance factor or the mechanism of resistance utilized serum-resistant and serum-sensitive clinical isolates (8,54,55), and only in the past few years have isogenic parent-mutant pairs been tested (3,14,22,36,60). These studies indicated that there were several mutations affecting The results of the present study showed that UspA2 is directly involved in the expression of serum resistance by some strains of M. catarrhalis.…”
Section: Discussionmentioning
confidence: 81%
“…The CD outer membrane protein (33) has been shown to bind middle ear mucin in vitro (51), a function that could be involved in the colonization process or in the development of otitis media. The UspA1 protein has been shown to be an adhesin, at least in vitro (38), whereas both the UspA2 protein (38) and outer membrane protein E (50) have been implicated in serum resistance. Both UspA1 and UspA2, consistent with their functional activities, have been localized to the surface of M. catarrhalis, where they are accessible to antibodies (2,45).…”
mentioning
confidence: 99%
“…Seven MAbs which recognize epitopes on OMP E have been described previously (4,17). MAb 2E11 was developed from a fusion in which mice were immunized subcutaneously with 50 g of purified recombinant OMP E from M. catarrhalis strain ATCC 25240 (4) with incomplete Freund's adjuvant on days 0 and 14.…”
Section: Methodsmentioning
confidence: 99%
“…The protein is expressed in all strains of M. catarrhalis studied thus far (2,4,16). Three independent lines of experiments indicate that OMP E contains epitopes on the bacterial surface; these include adsorption studies with polyclonal antisera raised to whole bacterial cells (16), immunofluorescence microscopy with polyclonal antisera raised to purified OMP E (4), and flow cytometry with monoclonal antibodies (MAbs) (4,17).…”
mentioning
confidence: 99%